Designing a Culinary Village With Eco-Architecture Approach in Kampung Badur - Dwira Nirfalini Aulia; Namira Sani (Talenta Publisher, 2018)
Based on data from Dinas Perumahan dan Permukiman Kota Medan, Kampung Badur is one of housings and settlements with very poor slum level. This statement is constituted by irregular home plots, disobedience to house building regulations, and uninhabitable physical condition of buildings and environments but Kampung Badur also has some potential in social, economic and cultural aspects that can be developed. Looking at the situations in Kampung Badur, this area needs to be rearranged into a better area by exploiting the existing potential to become a commercial area like culinary area, designing decent residential model, adding facilities and public spaces.